Removing the race section in official documents used by government and private sectors as a gesture for sustaining national harmony: a Malaysian's perspective - Ismail, Ismi Arif; Dahalan, Dzuhailmi; Abdullah, Haslinda; Suandi, Turiman; Krauss, Steven Eric; Kamarudin, Nurul Akhtar (Human Resource Management Academic Research Society, 2017)
This paper examines the perception of Malaysian on the proposed removal of race section in official documents used by government and private organizations. The paper employed mixed method research paradigm. A total sample of 1513 Malaysian residents in Peninsular Malaysia was randomly selected from the whole population and data was collected using structured set of instruments, focus group interview and document analysis. The data was analysed using IBM SPSS software version 24 for both descriptive and inferential analysis. The findings shows that majority of Peninsular Malaysians did not support the proposal to remove race section in the official government and private documents. However, the findings revealed that Chinese and Indian communities are keen to support the proposal of removing the race section in the official government and private documents compared to the Malays, so also Sabah/Sarawak Bumiputera living here in Peninsular. Moreover, Gen Z also support the proposal, which contradict from the Baby Boomer, Gen X and Gen Y. Based on the findings of this paper, the removal of the race section in the official government and private documents, can spark race sensitivity and polemic among the multiple race of Malaysia. The paper, however recommends allowing the race section in the official government and private documents in Malaysia.